Penerimaan Diri Pada Generasi Sandwich - Indah Puji Rahayu; Hastuti Rifayani (Pusat Riset dan Inovasi Nasional, 2024)
The sandwich generation, individuals transitioning between providing support for their elderly parents while still taking care of their own children, potentially face numerous challenges, both physically and emotionally. This phenomenon has garnered attention as the burdens on the sandwich generation increase, prompting this research to analyze how they navigate these dual roles and the psychological impact on their self-acceptance. The research aims to understand how the sandwich generation manages these dual roles and their implications for self-acceptance, taking into consideration psychological factors. To achieve this, the research utilizes a qualitative methodology based on in-depth interviews with participants selected based on specific criteria from this sandwich generation. The interview results indicate that the sandwich generation faces a heavy burden in balancing their dual roles, impacting their self-acceptance as they often feel inadequate in each role they undertake. However, there is a strong tendency for them to accept this condition as part of their responsibility, albeit with a high emotional burden. These findings underscore the need for a more sensitive and holistic approach in providing support to the sandwich generation.